Electro-mechanical coupling hydrogel microsphere with stable mechanical property and low loss transduction as well as preparation method and application of electro-mechanical coupling hydrogel microsphere

By introducing slip ring structures and conductive polypyrrole networks into piezoelectric hydrogels, stress-electrically coupled hydrogel microspheres are constructed, which solves the problems of high energy dissipation and poor mechanical stability of existing materials during force-electric transduction, and achieves effective repair of low-loss transduction and osteoarthritis.

CN119661873AActive Publication Date: 2025-03-21RUIJIN HOSPITAL AFFILIATED TO SHANGHAI JIAO TONG UNIV SCHOOL OF MEDICINE +1

Patent Information

Application Number
CN202411754263.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-21
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing piezoelectric hydrogel materials have excessive energy dissipation during the force-electric transduction process and poor mechanical stability performance, which cannot effectively achieve low-loss transduction between tissues and ideal repair effects for osteoarthritis.

Method used

By introducing supramolecular polyrothane and conductive polypyrrole networks with slip ring structures, stress-electrically coupled hydrogel microspheres are constructed, and the molecular slip mechanism of slip ring structures is used to store and release mechanical energy, improve electron transfer efficiency, and reduce energy loss.

Benefits of technology

It significantly improves the stress-electric coupling efficiency, reduces the energy dissipation rate to 43%, enhances the stability of mechanical properties, and improves the therapeutic effect of osteoarthritis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661873A_ABST
    Figure CN119661873A_ABST
Patent Text Reader

Abstract

The invention provides a mechano-electric coupling hydrogel microsphere with stable mechanical property and low loss transduction as well as a preparation method and application thereof, and belongs to the technical field of tissue engineering bioremediation materials. According to the invention, supramolecular engineering and microfluidic technologies are utilized, and a slip ring structure polyrotaxane and conductive polypyrrole network is introduced to construct stress-electric coupling hydrogel microspheres. The molecular slippage mechanism of the slip ring structure stores and releases mechanical energy to reduce mechanical loss, and the conjugated pi-electron movement in the conductive network improves the electron transfer efficiency in the microsphere, so that the loss in stress-electricity conversion is reduced for the first time. Compared with the traditional piezoelectric hydrogel microspheres, the stress-electric coupling efficiency of the low-dissipation microspheres is improved by 2.3 times, and the energy dissipation rate is reduced to 43%. The mechano-electric coupling hydrogel microspheres can reduce cartilage injury of rats, improve behavior results and promote treatment of osteoarthritis by recovering low-loss transduction between tissues.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of tissue engineering biorepair materials, and specifically relates to a mechanoelectric coupling hydrogel microsphere with stable mechanical properties and low-loss transduction, and a preparation method and application thereof. Background Art

[0002] Energy conversion in the human body involves various forms of mutual conversion and synergy, including mechanical energy, electrical energy, and chemical energy. For example, in the energy conversion process of articular cartilage, the piezoelectric properties of cartilage can convert mechanical energy (such as compression force during walking) into electrical energy. In addition, the electrical signals generated by cartilage tissue through the piezoelectric effect can change the intracellular electrochemical gradient and ion channel activity, thereby affecting the intracellular chemical reactions (chemical energy), such as intracellular pH, ion concentration, and the activity of other signaling molecules, thereby further regulating cell behavior and tissue function. Therefore, electromechanical energy conversion plays an important guiding role in tissue regeneration and functional recovery.

[0003] As a natural force-electric coupling agent, the extracellular matrix is ​​the main medium for electromechanical conversion in biological tissues, and it has low-loss energy transduction properties. The electrical signals generated by low-loss transduction between tissues have been shown to be an important means of regulating cell fate and play a vital role in optimizing the microenvironment of tissue repair and regeneration. Electrical signals regulate the reconstruction of damaged tissues by activating ion channels and downstream cell signals, thereby guiding cell behavior, especially the migration and differentiation of stem cells. In addition, studies have found that the immunomodulatory effect induced by electrical signals plays an important role in tissue repair.

[0004] However, damage or degradation of the extracellular matrix can impair the natural low-loss transduction properties of the tissue, resulting in a large amount of energy loss during the electromechanical conversion process in the tissue. This high energy transduction loss caused by tissue damage will not only lead to cell dysfunction at the site of injury, but may also aggravate tissue damage. Therefore, it is particularly important to develop a mechano-electric coupling functional repair material that can reduce the high transduction loss at the site of injury to restore the original low-loss properties of the tissue and accelerate the repair and regeneration of damaged tissue. However, in electromechanical energy conversion systems, reducing the energy transduction loss of functional materials has always been a major challenge.

[0005] In order to effectively reduce the transduction loss at the site of tissue damage, piezoelectric hydrogel based on force-electric coupling is one of the most representative functional materials. The researchers encapsulated barium titanate nanoparticles in the hydrogel to make the hydrogel have piezoelectric properties. This piezoelectric hydrogel deforms under mechanical stress or other physical stimulation, stores mechanical energy and applies pressure to the piezoelectric particles (mechanical conduction); when the piezoelectric particles are compressed, the positive and negative charge centers in their crystal structure are relatively displaced, forming an internal electric field, which converts the mechanical energy absorbed by the hydrogel into electrical energy (energy conversion); this electrical energy is transmitted to the surrounding biological tissues in the form of electrical signals (electrical transduction), activating the energy metabolism and immune regulation of stem cells, thereby achieving rapid repair of damaged tissues.

[0006] Despite this, the piezoelectric hydrogels currently developed still cannot avoid the characteristics of high energy dissipation. The reason is that when the piezoelectric hydrogel is subjected to external force, the covalent bonds and ionic bonds in the hydrogel network break, absorb mechanical energy, and then dissipate it in the form of heat, resulting in a large amount of energy loss. In addition, the cross-linking points in the hydrogel network limit the freedom of movement of the molecular chain segments, resulting in increased intermolecular friction and energy dissipation under stress. These factors together lead to excessive energy loss in piezoelectric hydrogels when converting mechanical energy into electrical energy, and they cannot have the low energy dissipation characteristics of natural extracellular matrix. Therefore, increasing the freedom of movement of molecular chain segments in piezoelectric hydrogels, reducing related bond breakage and intermolecular friction, and reducing mechanical losses are the key to restoring low-loss transduction in tissues.

[0007] On the other hand, as a key component for restoring low-loss transduction between tissues, the strength of the electrical signal conducted by the hydrogel directly affects its therapeutic effect. Although piezoelectric hydrogels can effectively convert mechanical energy into electrical energy, the lack of freely moving carriers within the polymer molecules and the three-dimensional cross-linked network structure limit the free movement of carriers, resulting in large electrical losses during the conduction process. Such high electrical losses hinder the transmission of electrical signals to the surrounding damaged tissues, greatly limiting its therapeutic effect. Therefore, further improving the electron migration efficiency of piezoelectric hydrogels, reducing electrical losses, and constructing a coupling system with low electromechanical losses are necessary conditions for achieving the development of piezoelectric hydrogels with high repair properties.

[0008] However, the various hydrogel functional materials currently developed, when used for repairing bone tissue damage, generally have high energy transduction loss and insufficient conductivity of piezoelectric hydrogels, which cannot achieve the low-loss transduction characteristics of natural tissues and efficiently repair damaged tissues. On the other hand, the existing piezoelectric hydrogels also have poor mechanical stability. Under cyclic stress stimulation, the hydrogel material is prone to cracks, resulting in a significant decrease in mechanical properties, and cannot provide sufficient mechanical support for the repair of bone tissue, thereby greatly reducing the repair effect of damaged bone tissue in the later stage.

[0009] Chinese patent document CN 109627461 B (Announcement Date: 2021.1.19) discloses a polypyrrole nanocomposite conductive hydrogel, which is obtained by modifying polypyrrole with dopamine to obtain polypyrrole nanomaterials. Although the mechanical properties and stability of the conductive hydrogel are improved, it is not a piezoelectric hydrogel and does not have piezoelectric properties, and cannot achieve the stability of mechanical properties during force-electric transduction. At the same time, the conductive hydrogel is similar to ordinary piezoelectric hydrogels, and there are still problems such as excessive mechanical loss and excessive energy dissipation during force-electric transduction.

[0010] Chinese patent document CN 115581813 A (publication date: 2023.1.10) discloses the application of a piezoelectric hydrogel as bone glue, which can generate a continuous force-electric response microenvironment under ultrasonic precision loading to achieve regenerative repair of bone defects. However, the mechanical properties of the piezoelectric hydrogel are poor, and its cyclic stability during the piezoelectric stress process is poor. It is prone to cracks under stress, and the mechanical properties drop significantly. At the same time, the piezoelectric hydrogel also has the problem of high energy transduction dissipation and poor bone repair effect.

[0011] It can be seen that the existing hydrogel materials have problems such as large electromechanical transduction loss and excessive energy dissipation when preparing piezoelectric hydrogels; and the mechanical properties of the current piezoelectric hydrogels are relatively poorly stable and are prone to cracking under stress cycles, resulting in a significant decrease in mechanical properties.

[0012] Therefore, how to improve the mechanical properties stability of piezoelectric hydrogel materials while reducing their energy dissipation, and reduce the energy transduction loss of hydrogel materials in electromechanical energy conversion systems to provide better tissue damage repair effects has become a technical problem that needs to be solved urgently. Summary of the invention

[0013] The present invention is to solve the above technical problems, thereby providing a mechanoelectric coupling hydrogel microsphere with stable mechanical properties and low-loss transduction, and its preparation method and application. The technical objectives of the present invention are: first, to solve the problem of excessive energy dissipation in the mechanoelectric transduction process of existing piezoelectric hydrogels; second, to solve the problem that the mechanical stability of existing piezoelectric hydrogel materials is poor, cracks are prone to occur under cyclic stress, and the mechanical properties drop significantly; third, to solve the problem that the existing piezoelectric hydrogel has an unsatisfactory repair effect on damaged tissues such as osteoarthritis.

[0014] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0015] The present invention first provides a method for preparing mechanoelectric coupling hydrogel microspheres with stable mechanical properties and low loss transduction, comprising the following steps:

[0016] (1) preparing a pseudopolyrotaxane using α-cyclodextrin and polyethylene glycol, and then reacting with itaconic anhydride to prepare PEG-α-CD-IA pseudopolyrotaxane;

[0017] (2) using PEG-α-CD-IA pseudopolyrotaxane as a crosslinker, mixing it with GelMA solution, barium titanate nanoparticles and a photoinitiator to prepare an aqueous solution, and crosslinking it with the oil solution under ultraviolet light through a microfluidic device to obtain hydrogel microspheres;

[0018] (3) The hydrogel microspheres are mixed with pyrrole monomer and ammonium persulfate to undergo a polymerization reaction to prepare electromechanically coupled hydrogel microspheres.

[0019] The preparation method provided by the present invention firstly synthesizes a polyrotaxane with a sliding ring structure using cyclohexane, α-cyclodextrin and PEG as raw materials as a crosslinking agent. Then, barium titanate piezoelectric nanoparticles are introduced to construct methacryloyl gelatin (GelMA) hydrogel microspheres. In addition, free radical polymerization and π-π conjugation are used to introduce a polypyro conductive polymer network to successfully prepare sliding ring stress-electric gel microspheres (P-LMS) with low mechanical and electrical losses.

[0020] It is well known that high conduction loss at the site of tissue damage hinders its repair, and the high dissipation characteristics of piezoelectric biomaterials in mechanical and electrical conversion are a bottleneck challenge. The inventors used supramolecular engineering and microfluidics to introduce a sliding ring structure polyrotaxane and a conductive polypyrrole network to construct stress-electric coupling hydrogel microspheres. The molecular slip mechanism of the sliding ring structure stores and releases mechanical energy, reducing mechanical losses, while the conjugated π-electron movement in the conductive network improves the efficiency of electron transfer inside the microspheres, thereby reducing the losses in stress-electric conversion for the first time. Compared with traditional piezoelectric hydrogel microspheres, the stress-electric coupling efficiency of the low-dissipation microspheres of the mechanoelectric coupling hydrogel microspheres of the present invention is increased by 2.3 times, and the energy dissipation rate is reduced to 43%. At the cellular and molecular levels, it was found that the electrical signals generated by the low-loss transduction of stress-electric coupling hydrogel microspheres triggered the influx of calcium ions in stem cells, upregulated the cAMP and Wnt / β-catenin signaling pathways, and promoted chondrogenic differentiation. The enhanced electrical signals also regulate the transition of macrophages to the M2 phenotype, remodeling inflammation and promoting tissue repair. In vivo experiments showed that low-dissipation hydrogel microspheres alleviated cartilage damage in rats and improved behavioral outcomes by restoring low-loss intertissue transduction, promoting the treatment of osteoarthritis (OA).

[0021] As shown in the research results of the embodiments of the present invention, the electromechanical coupling hydrogel microspheres of the present invention have the following advantages:

[0022] 1. Even if ordinary hydrogels are modified with polypyrrole and polyrotaxane to increase mechanical properties, it is still impossible to reduce energy dissipation. Therefore, the present invention achieves the effect of greatly reducing the energy dissipation of the hydrogel by using polypyrrole and polyrotaxane in piezoelectric hydrogel (containing BTO), while the energy dissipation of traditional piezoelectric hydrogels that have not been modified by the above means is relatively high.

[0023] 2. Traditional piezoelectric hydrogels exhibit poor mechanical stability, are prone to cracking under cyclic stress, and have a large decrease in mechanical properties. However, after the present invention uses polypyrrole and polyrotaxane to modify the piezoelectric hydrogel, the mechanical performance stability of the material is greatly improved. After multiple cycles of application, the mechanical strength is basically unchanged and the stability is better.

[0024] 3. Compared with traditional piezoelectric hydrogels, the mechanoelectrically coupled hydrogel microspheres of the present invention have better repair effects on osteoarthritis.

[0025] Furthermore, the weight ratio of α-cyclodextrin to polyethylene glycol in step (1) is 4:1.

[0026] Furthermore, in step (1), the weight ratio of the pseudopolyrotaxane to itaconic anhydride is 1:1.

[0027] Furthermore, the reaction conditions in step (1) are reflux reaction at 60° C. for 6 hours.

[0028] Furthermore, the barium titanate nanoparticles in step (2) are prepared from anhydrous ethanol, Ti(OC4H9)4, Ba(OH)2·8H2O and H2O2 by a hydrothermal synthesis method.

[0029] Furthermore, the weight ratio of PEG-α-CD-IA, GelMA, barium titanate nanoparticles and photoinitiator in step (2) is 1:10:5:1.

[0030] Furthermore, in step (3), the weight ratio of the hydrogel microspheres, pyrrole monomer and ammonium persulfate is 10:1:1.

[0031] The second object of the present invention is to provide electromechanical coupling hydrogel microspheres prepared by any of the methods described above, which have the characteristics of stable mechanical properties and low-loss transduction, and can more effectively promote the treatment of osteoarthritis.

[0032] The third object of the present invention is to provide the use of the above-mentioned electromechanical coupling hydrogel microspheres in the preparation of tissue damage repair materials, specifically, for the treatment of osteoarthritis.

[0033] The beneficial effects of the present invention are as follows:

[0034] The present invention uses supramolecular engineering and microfluidics to construct a supramolecular sliding ring structure of force-electric coupling hydrogel microspheres to restore low-loss transduction between tissues. The force-electric coupling hydrogel microspheres of the present invention have been proven by in vitro and in vivo experiments to promote cartilage regeneration by restoring low-loss stress-electric coupling of articular cartilage. In addition, the device also has important potential application value in the regeneration of mechanically sensitive tissues such as bone, muscle and heart. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of force-electric coupling hydrogel microspheres for low-loss transduction between tissues; A) Preparation process of P-LMS; B) Mechanism of P-LMS to reduce mechanical and electrical losses; C) Mechanism of restoring low-loss tissue conduction in osteoarthritis model.

[0036] Figure 2 Characterization of force-electric coupling hydrogel microspheres; A) Schematic diagram of the preparation of tetragonal piezoelectric nanoparticles; B) SEM and AFM images of barium titanate and its lattice diffraction analysis; C) EDS elemental analysis; D) amplitude and phase images of piezoelectric force microscopy (PFM) analysis; E) XRD spectrum; F, G, H) butterfly ring, hysteresis loop, D33 curve; 1) molecular structure and NMR spectrum of polyrotaxane; J) SEM image of LMS; K) degradation image; L) particle size analysis; M) FTIR spectrum.

[0037] Figure 3 Low-loss transduction and stress-electric coupling characteristics of piezoelectric hydrogel microspheres; A) Schematic diagram of mechanical property test of low-loss conductive hydrogel; B) tensile stress-strain curve and Young's modulus of gel; C) fracture toughness; and D) stress relaxation curve of hydrogel at 100% strain; E) storage modulus (G') and loss modulus (G") between 1-100 angular frequencies; F) stretching and cyclic tests of hydrogel under different strains; G) stretching and cyclic tests of P-LMS under different strains; H) conductivity and resistance of hydrogel samples; I) schematic diagram of electrical signal output detection; J) open circuit voltage and short circuit current of hydrogel samples under ultrasonic stimulation; K) open circuit voltage of hydrogel samples under mechanical load.

[0038] Figure 4Effects of force-electric coupling hydrogel microspheres on chondrogenic differentiation of bone marrow mesenchymal stem cells; A) Live-dead staining of different groups of mesenchymal stem cells at 1, 3, and 5 days (dead cells and live cells are labeled differently); B) Schematic diagram of hydrogel microspheres mediating chondrogenic differentiation of bone marrow mesenchymal stem cells in vitro; C) SEM images of different groups of mesenchymal stem cells on microspheres; D) Immunofluorescence staining of type II collagen; E) Alcian blue staining of bone marrow mesenchymal stem cells; F) ACAN, G) type II collagen, H) Sox9 gene expression levels in bone marrow mesenchymal stem cells after 14 days of chondrogenic differentiation; I) Quantitative analysis of glycosaminoglycan expression; (n=6, NS, no significant difference, *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001).

[0039] Figure 5 Potential molecular pathways for chondrogenic differentiation of bone marrow mesenchymal stem cells; A) PCA analysis of transcriptome data of bone marrow mesenchymal stem cells; B) Volcano plot of differentially expressed genes; C) Heat map of differential expression of the top 25 up-regulated and down-regulated genes; D) Ramp3 biological function network constructed based on GeneMANIA (different labels in each circle correspond to different signal pathways, and different labels in the connecting lines correspond to different gene relationships); E) GO and KEGG enrichment analysis of all up-regulated genes.

[0040] Figure 6 Figure 3 Potential immunomodulatory effects of piezoelectric hydrogel microspheres on macrophages; A) F480 / FITC immunofluorescence staining of RAW264.7 cells co-cultured with microspheres on day 5, scale bar: 20 μm; B, C) iNOS / CD206 immunofluorescence staining and quantitative analysis of RAW264.7 cells co-cultured with microspheres on day 5, scale bar: 60 μm; D, E) Scatter plot and quantitative analysis of RAW264.7 cell surface markers CD206 and CCR7 by flow cytometry; F) CCR7, IL-6, CD206, IL-10 gene expression levels; (n=6, NS, no significant difference, *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001).

[0041] Figure 7In vivo evaluation of the therapeutic effect of osteoarthritis by imaging and gait analysis; A) Schematic diagram of OA rat molding; B) Micro CT three-dimensional reconstruction image; C) Magnetic resonance scanning image; D) Coronal and sagittal images of X-rays; E) Heat map of rat motion trajectory analysis; F) Rat motion gait analysis, normal feet and experimental feet are marked differently; G) Relative step length of rats in each group; HL) Rat knee joint bone measurement analysis; osteophyte volume, bone density, BV / TV, Tb.Pf and SBP.Th; (n=6, NS, no significant difference, *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001).

[0042] Figure 8 Tissue staining and scoring were used to evaluate the in vivo therapeutic effect of osteoarthritis; A) H&E staining; B) Toluidine blue staining; C) Immunofluorescence staining of type II collagen; D) Immunofluorescence staining of MMP-13; E) Percentage of type II collagen-positive cells; F) Percentage of MMP-13-positive cells; G) OARSI score of rat knee joint; H) Mankin score of rat knee joint based on histological staining images; (n=6, NS, no significant difference, *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001).

[0043] Fig. 9 is the XPS spectrum of P-LMS.

[0044] Fig.10 EDS elemental spectrum analysis of P-LMS hydrogel microspheres.

[0045] Fig.11 This is the degradation curve of P-LMS hydrogel microspheres.

[0046] Fig.12 The stretching and strain curves of MS hydrogel under different strains.

[0047] Fig.13 Residual strain and hysteresis strain of P-LMS hydrogel under cyclic test.

[0048] Fig.14 Lighting lamp for P-MS and P-LMS NS-rG@VEGF ICs in dry environment.

[0049] Fig.15 The stability of P-LMS conductivity.

[0050] Fig.16 is the short-circuit current of the hydrogel sample under mechanical load.

[0051] Fig.17Dead cell staining of bone marrow mesenchymal stem cells after US stimulation for 1, 3, and 5 days.

[0052] Fig.18 The following are: A) quantitative analysis of live cells of bone marrow mesenchymal stem cells co-cultured with samples for 1, 3, and 5 days and B) CCK8 assay; (n=3, NS, no statistically significant difference).

[0053] Fig.19 Potential molecular pathways for chondrogenic differentiation of macrophages; A) Up-regulated genes and B) down-regulated genes by KEGG enrichment analysis; C) GO enrichment analysis of all up-regulated and down-regulated genes; D) Schematic diagram of potential molecular pathways; E) Concentrations of pro-inflammatory cytokine IL-1β and anti-inflammatory cytokine IL-10; (n=3, NS, no significant difference, *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001).

[0054] Fig. 20 Coronal and sagittal X-ray images of the different treatment groups.

[0055] Fig.21 For rat movement trajectory analysis.

[0056] Fig. 22 H&E staining of OA rat organs.

[0057] Fig.23 A) Immunofluorescence staining of CD86 and CD206 and B) quantitative analysis of RAW264.7 cells in synovial tissue; (n=3, NS, no significant difference, *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001). DETAILED DESCRIPTION

[0058] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.

[0059] Example 1

[0060] 1. Experimental methods and characterization

[0061] 1. Preparation and characterization of piezoelectric nanoparticles

[0062] Piezoelectric tetragonal barium titanate nanoparticles were prepared by hydrothermal synthesis. 40 mL of anhydrous ethanol, 2 mL of Ti(OC4H9)4, 2 g of Ba(OH)2·8H2O and 0.8 mL of H2O2 were added to a polytetrafluoroethylene-lined autoclave, stirred magnetically at 70°C for 30 minutes, and then heated in an oven at 180°C for 24 hours. Barium titanate nanoparticles were obtained by suction filtration and washing.

[0063] The composition, crystal structure, microstructure and particle size distribution of the nanoparticles were analyzed by XRD, SEM-EDS, TEM and nanoparticle size analyzer. The piezoelectric properties of the nanoparticles were measured by piezoresponse force microscopy (PFM). The nanoparticles were coated on a 1×1 cm 2 The ITO conductive glass was used as the bottom electrode, and the piezoelectric response curve was obtained by using the dual AC resonance tracking PFM (DART-PFM) mode, and single-point spectrum measurement was performed.

[0064] 2. Synthesis and characterization of PEG-α-CD-IA crosslinker

[0065] First, dissolve 6.0222g of α-cyclodextrin and 1.5044g of polyethylene glycol in 100mL of distilled water, and place the mixture in a 4°C refrigerator overnight. Use a microfiltration membrane with a pore size of 0.45μm to vacuum filter for 1.5h, and dry at 60°C for 6h to obtain a pseudopolyrotaxane complex. Dissolve the pseudopolyrotaxane and 6.0225g of itaconic anhydride in 30ml of dimethyl sulfoxide to form a uniform solution, and reflux at 60°C for 6 hours. Next, add 50ml of acetone to the solution to form a white precipitate. The precipitate is filtered with a 45μm microporous membrane and washed with acetone three times. Finally, the precipitate is vacuum dried at 60°C for 18 hours to obtain the PEG-α-CD-IA pseudopolyrotaxane crosslinker. Use 1 H-NMR was used to analyze the chemical composition of the samples.

[0066] 3. Preparation and characterization of low-loss electro-electric coupling hydrogel microspheres

[0067] 10wt% gelatin and methacrylic anhydride were reacted in a carbonate buffer solution at pH = 9.0 for 3 hours. After the reaction, dialyzed for 2 days and then freeze-dried to obtain GelMA hydrogel. Then, GelMA, BTO, PEG-α-CD-IA, and photoinitiator LAP were dissolved in deionized water to prepare a solution. Paraffin oil and Span80 were mixed to prepare an oil phase solution, the flow rate ratio of the aqueous phase to the oil phase was adjusted in a microfluidic device at 60°C, and a cross-linking reaction was carried out under ultraviolet light to obtain hydrogel microspheres. Subsequently, the hydrogel microspheres were freeze-dried for further experiments.

[0068] The hydrogel microspheres were added to the aqueous solution of pyrrole monomers, stirred magnetically for 2 hours, and then ammonium persulfate was slowly added to initiate the polymerization of pyrrole, and reacted at 4°C for 8 hours to obtain low-loss conductive piezoelectric hydrogel microspheres (P-LMS). The same method was used to prepare piezoelectric hydrogel microspheres (P-MS) without PEG-α-CD-IA and polypyrrole.

[0069] The morphology and chemical composition of the microspheres were analyzed by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), energy dispersive spectrometry (EDS) and Fourier transform infrared spectroscopy (FTIR).

[0070] 4. Experiment on the force-electric coupling efficiency of hydrogel microspheres

[0071] In order to test the mechanical loss performance of piezoelectric hydrogel microspheres, the mechanical properties of the hydrogel were measured using a mechanical testing device. The stretching rate was kept constant at 100 mm / min. Young's modulus was based on the initial slope of the stress-strain result, and toughness was based on the integrated area of ​​the stress-strain curve at the fracture of the specimen. The hysteresis was defined by the overlap area of ​​the unloading curve with the x-axis relative to the overlap area of ​​the loading curve with the x-axis. The difference between 100% and this value gives the hysteresis. The storage modulus (G') and loss modulus (G") spectra of the hydrogel were measured using a rotational rheometer in frequency sweep mode at 25 °C. Stress relaxation tests were performed on the hydrogel samples at room temperature with a fixed strain of 10% and a frequency of 1 Hz. The conductivity of the hydrogel was tested using a digital potentiometer. The short-circuit voltage and open-circuit current of the hydrogel under ultrasonic and mechanical loading were measured using a digital oscilloscope.

[0072] 5. Cell culture

[0073] Mouse-derived macrophages (RAW264.7) and mesenchymal stem cells (BMSCs) were provided by the Shanghai Institute of Cell Biology. DMEM supplemented with 10% fetal bovine serum was used as the culture medium. 5% CO2 was added during incubation, and DMEM was replaced every 2-3 days. When bone marrow mesenchymal stem cells were co-cultured with piezoelectric microspheres in vitro, an ultrasonic therapy device was used as an external pressure stimulus to provide 0.5 W / cm 2 , 1MHz, 50% duty cycle ultrasound intensity. In order to simulate the in vivo application scenario, low adhesion plates were used for cell culture. Bone marrow mesenchymal stem cells were co-cultured with different microspheres in chondrogenic differentiation medium for 14 days, and ultrasound stimulation was performed for 5 minutes every day.

[0074] 6. Cytocompatibility

[0075] In order to evaluate the effect of the samples on the viability of bone marrow mesenchymal stem cells, live / dead staining combined with fluorescence microscopy was used. First, mesenchymal stem cells (initial concentration of 1.5×10 4 mL -1) were cultured in the lower chamber of a 24-well plate, and the microspheres were placed in the upper chamber (pore size 0.4 μm, Corning, USA). After 1, 3, and 5 days of culture, 200 μL of working solution (Calcein AM / PI, Beyotime, China) was added and cultured with the cells for 30 minutes. The cells were then observed under a fluorescence microscope. The number of cells showing green fluorescence and red fluorescence was counted to evaluate cell viability. In addition, the CCK-8 method was used to evaluate the effect of bone marrow mesenchymal stem cells on the proliferation of microspheres. Mesenchymal stem cells (BMSCs, initial concentration 0.3×10 4 mL -1 ) were cultured in a 96-well plate in the lower chamber, and microspheres (pore size 0.4 μm) were placed in the upper chamber. After 1, 3, and 5 days of culture, CCK-8 solution (10 μL) was placed in the wells. After 1 hour of incubation, the absorbance was measured at 450 nm using a FlexStation 3 microplate reader (Molecular Devices, Japan) to evaluate the proliferation of bone marrow mesenchymal stem cells.

[0076] 7. Immunofluorescence staining

[0077] (1) After 14 days of co-culture, the samples were fixed with paraformaldehyde. Subsequently, the samples were incubated with blocking solution containing Triton X-100 for 30 minutes. The samples were incubated with diluted primary and secondary antibodies according to standard protocols. Then, Actin-Tracker Red-555 was used to stain the cytoskeleton and DAPI was used to stain the nucleus. Finally, the samples were observed and imaged using a laser scanning confocal microscope (LSCM).

[0078] (2) Alcian blue staining

[0079] Alcian blue staining was used to detect the expression of glycosaminoglycans (GAGs) after 14 days of co-culture. Considering that light cannot penetrate the modified piezoelectric microspheres in a three-dimensional cell culture system, the microspheres and cells were co-cultured in two dimensions on the plane of the well plate. The cells were fixed with paraformaldehyde and incubated with Alcian blue at room temperature for 30 minutes. After thorough washing with water, the samples were observed using an optical microscope.

[0080] (3) RT-qPCR

[0081] After 14 days of cell culture, RNA was isolated using TRIzol. Then, PrimeScript TM RNA was reverse transcribed into complementary DNA (cDNA) using the RT Master Mix Kit (Takara). Premix Ex Taq TMII and primers were mixed with cDNA and qPCR was performed using fluorescent staining. The target genes included aggregin (ACAN), type II collagen (COL 2), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and SOX-9. The primer sequences are shown in Table 1.

[0082] Raw264.7 cells (initial concentration 3×10 4 mL -1 ) were cultured in 24-well plates and stimulated with LPS (100 ng / mL) for 24 h. The microspheres were then placed in the upper chamber and co-cultured with the cells for 5 days, with ultrasound stimulation for 15 minutes every day. The cells were stained with F480 (Beyotime, China), Phalloidin and DAPI (Beyotime, China), and the morphology of macrophages was observed using LSCM.

[0083] Table 1 Primers used for chondrogenic differentiation of bone marrow mesenchymal stem cells

[0084]

[0085]

[0086] 8. Macrophage phenotype assessment

[0087] Immunofluorescence staining was used to stain iNOS and CD206 in co-cultured Raw264.76 cells, using the same method as above, and the cells were observed and photographed using LSCM. In addition, cells were stained with phycoerythrin (PE) / Cy7-coupled CCR7 and allophycocyanin (APC)-coupled CD206, and the proportion of M1 and M2 macrophages was analyzed by flow cytometry. Total RNA was isolated from co-cultured cells using the TRIzol method. ACTB was used as a housekeeping gene, and the primer sequences for IL-6, CCR7, CD206, and IL-10 are listed in Table 2.

[0088] Table 2 Primers for Raw264.7 macrophage phenotype

[0089]

[0090] 9. Animal Modeling

[0091] Male SD rats weighing approximately 200-250 g underwent DMM surgery to establish a chronic inflammatory OA model. Briefly, after anesthetizing the rats, a longitudinal incision was made along the medial edge of the right knee patella to expose the joint cavity. In addition to processing the medial meniscus ligament, surgery to separate and remove the medial meniscus was also performed. The incision was closed layer by layer. No tissue damage occurred in the sham group. 72 rats were divided into two treatment time points (2 months and 4 months) and randomly divided into five intervention groups: sham group (Sham), PBS treatment group, MS group, P-MS group, and P-LMS group. Immediately after surgery, 10 μL of microsphere suspension was injected once every 2 weeks.

[0092] 10. Behavioral Assessment

[0093] Knee pain in rats was first assessed before and 3 months after surgery. Briefly, rats were housed in a cage with a wire mesh floor, and a von Frey wire (Shanghai Yuyan Instrument Co., Ltd.) (0.008 g-180 g) was applied vertically to the metatarsal surface of the rat's hind paw until the wire bent. After waiting at least 5 seconds to observe whether the rat withdrew its paw, different filament sizes were tested until a change in response was observed. The stimulation was repeated 4 times, and the paw withdrawal threshold (50% withdrawal threshold) was recorded. For footprint analysis, the right paw of the modeling side rats was painted with red ink, and the left paw of the non-modeling side rats was painted with blue ink. Rats were placed at one end of a 1-meter-long black box, and their phototropism was used to encourage them to walk to the other end, and paw print images were collected. Rats were placed in a 1-meter square response box. After calming down, 6-min movement videos were recorded and analyzed using Smart 3.0 behavioral video recording and analysis software.

[0094] 11. Radiological evaluation

[0095] Three months after surgery, OA rats were maintained under isoflurane anesthesia with lower limbs immobilized, and the knee joints were imaged using small animal MRI (BioSpec 70 / 20USR, Bruker, Germany). In addition, anteroposterior and lateral X-ray images of the flexed knee joint were taken 3 months after surgery using a mammography device with an exposure of 95 mAs and a voltage of 30 kV. After euthanasia of rabbits and rats, knee joint specimens were obtained. The samples were scanned using Micro CT (μCT50, Scanco Medical, Switzerland) with parameters of 145 mA, 55 kVp, and 300 ms integration time. Three-dimensional images were generated using Scanco software, and three-dimensional analysis was performed to quantify the new bone volume and osteophyte volume at the defect site.

[0096] 12. Macroscopic evaluation of cartilage regeneration

[0097] The regeneration of the rabbit cartilage defect model was evaluated according to the International Cartilage Repair Society (ICRS) cartilage repair macroscopic evaluation criteria. Three independent professionals were invited to evaluate the obtained rabbit femoral specimens using a double-blind principle.

[0098] 13. Histology and Immunohistochemistry

[0099] After radiographic and macroscopic evaluation, specimens were stored in 4% paraformaldehyde. Hematoxylin and eosin (HE) and toluidine blue staining of the samples were performed according to the supplier's protocols to evaluate morphology and GAG distribution, respectively. Subsequently, for type II collagen and MMP13 immunofluorescence histochemistry, the specimens were stained with the respective antibodies according to the supplier's protocols.

[0100] 2. Experimental Results and Discussion

[0101] 1. Preparation and characterization of stress-electric coupling hydrogel microspheres

[0102] Tetragonal barium titanate (BTO) was used as the piezoelectric element of the hydrogel microspheres. Square barium titanate nanoparticles were successfully synthesized by hydrothermal synthesis. In order to observe the surface morphology of the nanoparticles, the particle size distribution and surface morphology of the synthesized BTO were analyzed by SEM, TEM and DLS. Figure 2 BTO exhibits a typical tetragonal phase morphology with a particle size of about 200 nm. In addition, the crystal structure of BTO was analyzed by XRD, and its diffraction peaks matched the standard PDF card of tetragonal barium titanate ( Figure 2 (E) In the 2θ range of 42-50°, a bimodal structure with tetragonal characteristics of barium titanate was observed, further confirming that the synthesized nanoparticles have a piezoelectric tetragonal structure.

[0103] To further investigate its piezoelectric properties, under an alternating electric field, PFM amplitude and phase images showed that the bright and dark regions of BTO matched well ( Figure 2 Butterfly loop and hysteresis loop ( Figure 2 Figures F and G show the polarization switching behavior of BTO under an applied electric field, confirming the piezoelectric effect. Further analysis of the D33 curve shows that the piezoelectric constant of BTO is about 10.97 pm / V ( Figure 2 Middle H).

[0104] Polyrotaxane polymer was synthesized using polyethylene glycol and α-cyclodextrin as raw materials, and polymerizable double bonds were introduced through esterification reaction of hydroxyl groups on cyclodextrin with itaconic anhydride. 1 H-NMR results ( Figure 2Figure 1) shows that the characteristic peak between 3.44-3.54 ppm is the methylene proton of PEG, while the signal near 4.71 ppm is the characteristic peak of α-cyclodextrin. In addition, the signal at 5.68 ppm is the characteristic peak of the proton on the double bond carbon atom of itaconic acid, which is the result of the reaction between itaconic anhydride and hydroxyl. These results indicate that the synthesis of polyrotaxane is successful.

[0105] Next, BTO was incorporated into the GelMA hydrogel using polyrotaxane as a crosslinker, and polypyrrole was further introduced through free radical polymerization. To verify the successful incorporation of BTO, polyrotaxane, and polypyrrole, the samples were analyzed by FTIR and XPS. The FTIR results showed that the vibration of the methoxyl group in the polyrotaxane (ether bond) was at 1086 cm -1 ) and polypyrrole (the stretching vibration of CN in the pyrrole ring is at 1443 cm -1 The characteristic peak ( Figure 2 The XPS results showed the characteristic peaks of nitrogen and barium, further confirming the successful preparation of the hydrogel ( Fig. 9 ). SEM images at different magnifications show that the microspheres have a porous spherical structure and BTO is evenly distributed on the hydrogel microspheres ( Figure 2 In addition, EDS detected the distribution of barium and titanium on the microspheres ( Fig.10 The biodegradability of the microspheres was observed by optical microscopy and weight loss method ( Figure 2 Middle K and Fig.11 ). As shown in the figure, the microspheres underwent significant degradation over time, and the quantitative experiment also showed a similar trend, with the degradation rate of the microspheres being 78% after 56 days.

[0106] 2. Low-loss transduction and stress-electric coupling efficiency test

[0107] First, the mechanical properties of the hydrogel samples were tested. Figure 3 As shown in Figures B and C, the addition of polyrotaxane significantly enhanced the fracture strength of the gel, increasing it from 35.9 kPa to 59.4 kPa, an increase of nearly 1.7 times; the elongation at break slightly decreased from 95.7% to 79.1%. These results show that the use of polyrotaxane as a cross-linking agent can effectively improve the mechanical properties of the hydrogel. Quantifying this result shows that the modulus of the P-LMS gel gradually increases and the corresponding elongation gradually decreases, indicating that this change further enhances the interaction or cross-linking density between the networks.

[0108] The fracture toughness of the gel shows that the fracture toughness of the gel from MS to P-MS and from LMS to P-LMS does not increase much, while the strength of the gel from P-MS to LMS increases significantly, indicating that BTO has no significant effect on the mechanical properties of the hydrogel, while the addition of the polyrotaxane conductive network significantly enhances the mechanical properties of the hydrogel. Next, the samples were subjected to stress relaxation tests ( Figure 3 D). It is noteworthy that the modulus retention of the P-LMS gel gradually increases, indicating that even under high shear (10%) conditions, the gel still maintains a high modulus value, indicating its strong shear resistance and low mechanical loss.

[0109] Perform a frequency sweep test on the gel, such as Figure 3 As shown in E. In the angular frequency range of 1 to 100, the storage modulus (G') of all samples is greater than the loss modulus (G"), demonstrating their solid-like properties. In addition, the moduli of all hydrogels show obvious frequency dependence, indicating that they have good viscoelastic properties.

[0110] The P-LMS was subjected to tensile and cyclic tests at different tensile rates and strains. Figure 3 As shown in Figure F, increasing the stretching rate from 50 mm / min to 200 mm / min by nearly 4 times has no obvious effect on the performance of the gel; its modulus and strength do not change significantly. This result proves that the gel is rate-insensitive and lays the foundation for its low hysteresis. Subsequently, the hysteresis performance was studied. The hysteresis rate is the difference between the integral area of ​​the loading and unloading curves and the strain; the higher the overlap, the smaller the residual strain and mechanical loss. Smaller hysteresis rate and residual strain effectively reflect the elasticity of the gel, and higher elasticity directly indicates smaller mechanical losses. The gel was subjected to cyclic loading and unloading tests at 5%, 10% and 20% strains, as shown in Figure 2. Figure 3 Medium G and Fig.12 As shown in Figure 2. In the tensile test, the MS hydrogel exhibited a large hysteresis loop, indicating high energy dissipation and significant internal friction. Regardless of the deformation size, the P-LMS showed a very low hysteresis rate, and the loading and unloading curves almost overlapped with an overlap rate of more than 95%, indicating that the mechanical loss during deformation was extremely low.

[0111] The low mechanical loss of a single stretch does not effectively reflect the performance of the gel under multiple deformations. Therefore, a continuous 500-cycle test was further conducted to test its mechanical loss tolerance. Fig.13As shown, the mechanical properties of the gel did not decrease significantly, and its hysteresis efficiency remained below 5% even after 500 repeated cycles. Despite undergoing up to 500 repeated deformation-recovery cycles, the gel still exhibited excellent elasticity, that is, low mechanical loss characteristics. These results can be attributed to the introduction of a sliding ring structure, which allows the polymer chains within the hydrogel to slide relatively freely, thereby increasing the material's strain capacity and effectively dispersing the applied stress. Under mechanical stress, the sliding ring structure acts like a "molecular pulley", which can freely adjust the internal tension to resist external loads and relieve stress concentration.

[0112] The electrical loss characteristics of the hydrogel medium are another important factor affecting its stress-electric coupling efficiency. The high electrical conductivity of the hydrogel can reduce the electrical energy loss during signal transmission, thereby better transmitting it to the surrounding tissue. The electrical conductivity of these hydrogels is as follows: Figure 3 As shown in Figure 2, the conductivity of P-LMS is significantly higher than that of other samples due to the incorporation of a polypyrrole conductive network, which enhances electron migration within the hydrogel network

[38] . It is noteworthy that when P-LMS is integrated into the circuit, the light bulb lights up, while the light bulb of P-MS is off ( Fig.14 ). The results show that P-LMS has good electrical conductivity.

[0113] Considering the potential influence of complex fluids and electrolytes in biological environments on the electrical properties of hydrogels, the conductivity stability of P-LMS was tested under culture medium conditions for 7 days ( Fig.15 ). The conductivity did not change significantly, indicating that it maintained its low electrical loss characteristics in the biological microenvironment. In order to detect the electromechanical coupling efficiency of the hydrogel, the short-circuit current and open-circuit voltage of the microspheres under ultrasound activation were evaluated. Figure 3 Middle J shows that no obvious electrical signal was detected for the MS electromechanical transducer. For the P-LMS stress-electrical transducer, at an ultrasonic power of 1 W / cm 2 When the mechanical force increases, the open circuit voltage is 198mV and the short circuit current is 52nA, which is 2.3 times that of the P-MS electromechanical conversion device. In addition, under the action of periodic constant force, the open circuit voltage and short circuit current of P-LMS increase with the increase of mechanical force ( Figure 3 Middle K and Fig.16 ). Compared with the GELMA piezoelectric hydrogel commonly used in research, the electromechanical transduction efficiency of P-LMS is significantly improved. During the stress-electric coupling process of P-LMS, the molecular sliding mechanism of the slip ring structure reduces the mechanical loss; the piezoelectric BTO realizes electromechanical conversion; the π-conjugated electron movement mechanism within the conductive network minimizes the electrical loss, thereby achieving low-loss energy transduction. These results confirm that the P-LMS electromechanical transduction device can effectively convert various external forces into electrical signals, making it a low-loss stress-electric coupling electromechanical transduction device.

[0114] 3. In vitro low-loss transduction-mechanical-electrical coupling mediates stem cell chondrogenic differentiation

[0115] We further investigated the effect of electrical signals generated by low-loss stress-electric coupling on OA cartilage repair, and selected bone marrow mesenchymal stem cells as a stem cell model to verify our hypothesis that piezoelectric electrical signals can induce mesenchymal stem cells to differentiate into chondrocyte phenotypes in vitro. We used GelMA hydrogel microspheres as a control group and used ultrasound (US) as the mechanical energy source for stress-electric coupling of hydrogel microspheres. In order to ensure the safety of ultrasound use, a frequency of 40 kHz and a power of 0.5 W / cm 2 The studies were conducted with low-intensity ultrasound. The ultrasound parameters used did not directly affect the chondrogenic differentiation of stem cells. Live / dead and CCK-8 assays were performed after 1, 3, and 5 days of co-culture with or without the extract. Figure 4 As shown in Figure A, the cell density increased with the extension of culture time, and only a small number of dead cells were observed during the culture period. The CCK-8 quantitative results were consistent with the live / dead staining trend, and the cell viability of each group was good, indicating that these hydrogel microspheres have good biocompatibility ( Fig.17 ).

[0116] Next, we studied the chondrogenic differentiation of BMSCs co-cultured with ultrasound-activated piezoelectric hydrogel microspheres. The results showed that BMSCs from the control, P-MS, and P-LMS exhibited a round / polygonal stem cell morphology, while BMSCs from P-MS+US and P-LMS+US exhibited a typical flat / spindle-shaped chondrocyte morphology ( Figure 4 Middle C). These results indicate that the electrical signal generated by ultrasound-activated piezoelectric coupled microspheres promotes chondrogenic differentiation of stem cells.

[0117] Glycosaminoglycans (GAGs) and Col2 are two major proteins in the extracellular matrix of cartilage. GAGs provide articular cartilage with resistance to compressive loads and the ability to conduct cell signaling, while type II collagen provides elasticity and mechanical strength. Figure 4 As shown in D and E, the cells on P-MS+US and P-LMS+US expressed type II collagen and GAG in large quantities. These results indicate that the local electrical signals generated by ultrasound-activated piezoelectric hydrogel microspheres play a vital role in inducing BMSC differentiation into chondrocytes, which is consistent with other studies that have used electrical signals to promote articular cartilage repair. In addition, the effect of hydrogel microspheres on the expression levels of four chondrocyte marker genes was also studied, and the results showed that the expression levels of the four marker genes in the P-MS+US and P-LMS+US groups were significantly increased compared with the Control, P-MS, and P-LMS groups. It is worth noting that the expression levels of the four chondrocyte marker genes on P-LMS+US were higher than those on P-MS+US( Figure 4This result indicates that the low-loss transduction property of P-LMS enables it to generate higher electrical signals under ultrasound stimulation, providing an optimal electrical microenvironment for stem cell chondrogenic differentiation.

[0118] To investigate the potential mechanisms and molecular pathways of low-loss transduction in the chondrogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), RNA-seq analysis was performed. By comparing the transcriptome changes between the Control group and the P-LMS+US group, the effects of P-LMS on stem cells and their potential molecular pathways were analyzed. Figure 5 As shown in A and B, there were significant differences in gene expression between the two groups. Differential expression analysis found that 60 genes were upregulated and 52 genes were downregulated in the P-LMS group (Log2FC>1, p<0.05). Among them, Ramp3, which affects cartilage differentiation and cellular energy metabolism, was significantly upregulated. Its main function is closely related to the expression of calcium-binding proteins, changes in calcium levels, G protein-coupled receptor signaling pathways, and cAMP signaling pathways ( Figure 5 C and D).

[0119] The biological function network of Ramp3 was constructed based on the GeneMANIA database, and GO enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were further performed on the up-regulated genes to explore the regulatory mechanism of P-LMS on bone marrow mesenchymal stem cells. Figure 5 As shown in E, GO analysis results showed that P-LMS can upregulate the expression of calcium-binding proteins and G protein-coupled receptor signaling pathways. In summary, we hypothesize that piezoelectric microspheres promote stem cell chondrogenic differentiation mainly by upregulating the cAMP signaling pathway through intracellular calcium influx.

[0120] 4. In vitro low-loss transduction-mechanical-electrical coupling to reconstruct the regenerative immune microenvironment

[0121] After LPS treatment to promote M1 polarization of macrophages for 48 hours, they were co-cultured with hydrogel microspheres in each group to verify their effects on macrophage polarization. F4 / 80 and F-actin fluorescence staining were used to observe the morphology of macrophage markers ( Figure 6 (A). Macrophages on P-MS+US and P-LMS+US showed a typical spindle-shaped morphology of M2 macrophages, while macrophages on the control group, P-MS, and P-LMS showed a round morphology, which is generally considered to be a characteristic of M1 macrophages. Immunofluorescence staining combined with flow cytometry was used to analyze specific markers of M1 macrophages (iNOS) and M2 macrophages (CD206) to evaluate the polarization trend ( Figure 6 In the P-MS+US and P-LMS+US groups, M2 polarization was significantly upregulated, while M1 polarization was significantly downregulated.

[0122] In order to further evaluate the production level of inflammatory factors, RT-qPCR and Elisa were used to detect the expression levels of related genes and cytokines ( Figure 6 Medium F and Fig.18 ). Compared with the non-electric signal microsphere group, the expression of pro-inflammatory marker genes and cytokines in the P-MS and P-LMS groups was significantly downregulated, and the expression of anti-inflammatory genes and cytokine marker genes was significantly upregulated. The effect of P-LMS+US on macrophages was further analyzed by RNA-Seq ( Figure 6 Medium F and Fig.19 ). Graphene oxide analysis showed significant enrichment of immune system pathways, especially those involved in immune system processes and innate immune responses, indicating a strong association between electrical signals generated by P-LMS and macrophage immune-related pathways. In addition, KEGG pathway enrichment analysis identified specific signaling pathways associated with macrophage phenotypic transformation. The results showed that inflammatory pathways associated with M1 macrophage polarization, such as cytokine-cytokine receptor interactions, MAPK, NF-kappa B, and TNF signaling pathways, were significantly inhibited in the P-LMS+US group. In contrast, anti-inflammatory pathways, especially the TGF-β signaling pathway associated with M2 macrophage polarization, were significantly upregulated. These differential expression changes suggest that the treatment regulates macrophage M2 subtype polarization by inhibiting inflammatory pathway activation and enhancing anti-inflammatory pathway activation.

[0123] These results indicate that the electrical signals generated by piezoelectric hydrogel microspheres can restore the functional balance of macrophages, thereby creating a good immune microenvironment. This may be due to the fact that the electrical signals generated by piezoelectric hydrogel microspheres balance macrophage polarization by inhibiting the expression of AKT2 and IRF5 in the PI3K-AKT signaling pathway. It is worth noting that compared with P-MS+US, P-LMS+US generated higher electrical signals by reducing the energy loss during stress-electric coupling, which is more conducive to the balance of macrophage polarization.

[0124] 5. Low-loss transduction force-electric coupling for the treatment of osteoarthritis

[0125] In vivo studies of low-loss transduction-mediated OA were conducted using stress-electric coupled hydrogel microspheres. A rat osteoarthritis model was established by surgically inducing destabilization of the medial meniscus (DMM). Four weeks after induction, PBS, MS (control group), P-MS, and P-LMS were injected every 2 weeks, and the therapeutic effect of the microspheres was evaluated 12 weeks after surgery. X-ray and Micro-CT three-dimensional analysis results showed ( Figure 7 B, C, D and Fig. 20), the PBS group and the control group showed severe osteoarthritis, manifested by obvious osteophyte formation, subchondral bone destruction, and joint space narrowing. In contrast, the P-MS and P-LMS treatment groups showed significantly reduced osteophyte formation, reduced subchondral bone destruction, and mild joint space narrowing. In addition, T2-weighted MRI results showed that the thickness of articular cartilage in the PBS treatment group was significantly reduced, while the cartilage thickness in the P-LMS group did not show a decrease, indicating that the treatment effect of OA was significant.

[0126] The subchondral bone mineral density parameters were then quantitatively analyzed. Compared with the PBS treatment group, BV / TV, BMD, Tb.Pf and SBP.Th in the P-MS and P-LMS treatment groups were significantly reduced, with the P-LMS group showing the most significant reduction ( Figure 7 OA rats showed a decrease in stride length and movement ability due to joint pain and cartilage damage. The therapeutic effect of OA was analyzed by examining the stride length and movement trajectory of OA rats ( Figure 7 E, F, G and Fig.21 ). Compared with the Sham group, the stride length and movement of the PBS and control groups were significantly reduced, indicating severe OA. The stride length and movement trajectory of rats in the P-MS and P-LMS treatment groups increased significantly, with the P-LMS group showing the most significant improvement, further demonstrating its significant effect in treating OA.

[0127] Histological staining and quantitative scoring were used to further evaluate the therapeutic effect of microspheres in each group on OA in vivo. HE staining results showed that the chondrocytes in the Sham group were neatly arranged and the cartilage surface was smooth and flat. The cartilage surface in the PBS-treated group was obviously rough and damaged, and the subchondral bone was eroded. The roughness and damage of the cartilage surface in the P-MS and P-LMS groups were improved, and the degenerative lesions were reduced. The cartilage morphology in the P-LMS-treated group was better ( Figure 8 In the histological staining results, OARSI and Mankin scores were used to evaluate the degree of cartilage damage. Compared with the Sham group, cartilage damage in the PBS, Control, P-MS, and P-LMS groups increased to varying degrees, with the P-LMS group showing the smallest increase ( Figure 8 G and H).

[0128] In order to evaluate the biosafety of microspheres, we performed HE staining on the heart, spleen, liver, lung and kidney of OA rats. The results showed that there was no obvious histological abnormality in each group, with good biosafety and compatibility ( Fig. 22 In addition, immunofluorescence analysis was used to evaluate the expression of type II collagen ( Figure 8C, E). Compared with the Sham group, the expression of Col2 was significantly decreased in the PBS group and the control group, moderately decreased in the P-LMS group and the P-MS group, and the P-LMS group had the least decrease in Col2 expression. In addition, the inflammatory cytokine matrix metalloproteinase 13 (MMP13) was detected by immunofluorescence. The expression level of MMP13 is low in normal cartilage, but high in the cartilage of patients with osteoarthritis. The results showed that the expression of MMP13 in the P-MS and P-LMS treatment groups was significantly lower than that in the other treatment groups, and the expression of P-LMS was lower than that of P-MS ( Figure 8 In addition, immunofluorescence staining of CD86 and CD206 was performed on the synovial tissue surrounding the samples to evaluate the trend of macrophage polarization ( Fig.23 ). The results showed that both P-MS and P-LMS treatment groups significantly reduced the M1 / M2 ratio of synovial tissue, with the P-LMS group having the lowest M1 / M2 ratio. These results further suggest that stress-electric coupling hydrogel microspheres restore the electrical microenvironment of cartilage, improve the immune microenvironment, and promote chondrogenic differentiation to treat osteoarthritis through low-loss transduction.

[0129] Conclusion

[0130] The present invention develops a force-electric coupling hydrogel microsphere with a sliding ring structure as a medium to reduce energy loss during electromechanical conversion and restore low-loss transduction between tissues. Force-electric coupling hydrogel microspheres were prepared by coupling polyhexane and polypyrrole. This mechanical conduction network based on the sliding of sliding ring molecules realizes efficient mechanical energy storage and transmission, reducing mechanical losses during stress-electric coupling. The conjugated π-electron movement of polypyrrole is used to achieve electrical energy conduction, reducing electrical losses during stress-electric coupling. Therefore, the device can effectively convert the mechanical energy of tissue movement into electrical energy and restore low-loss transduction between tissues. The stress-electric coupling efficiency is 2.3 times that of traditional piezoelectric hydrogels, and the energy dissipation is reduced to 43%. This low-loss transduction force-electric coupling promotes cartilage differentiation of stem cells, promotes regeneration and remodeling of the inflammatory microenvironment, and thus promotes the treatment of osteoarthritis. In summary, this study provides a potential therapeutic strategy for repairing various mechanically sensitive tissues.

Claims

1. A method for preparing mechanoelectrically coupled hydrogel microspheres with stable mechanical properties and low-loss transduction, characterized in that: The following steps are involved: (1) preparing a pseudopolyrotaxane using α-cyclodextrin and polyethylene glycol, and then reacting with itaconic anhydride to prepare PEG-α-CD-IA pseudopolyrotaxane; (2) using PEG-α-CD-IA pseudopolyrotaxane as a crosslinker, mixing it with GelMA solution, barium titanate nanoparticles and a photoinitiator to prepare an aqueous solution, and crosslinking it with the oil solution under ultraviolet light through a microfluidic device to obtain hydrogel microspheres; (3) The hydrogel microspheres are mixed with pyrrole monomer and ammonium persulfate to undergo a polymerization reaction to prepare electromechanically coupled hydrogel microspheres.

2. The preparation method according to claim 1, characterized in that: The weight ratio of α-cyclodextrin to polyethylene glycol in step (1) is 4:

1.

3. The preparation method according to claim 1, characterized in that: The weight ratio of the pseudopolyrotaxane to itaconic anhydride in step (1) is 1:

1.

4. The preparation method according to claim 1, characterized in that: The reaction conditions in step (1) are reflux reaction at 60° C. for 6 hours.

5. The preparation method according to claim 1, characterized in that: The barium titanate nanoparticles described in step (2) are prepared from anhydrous ethanol, Ti(OC4H9)4, Ba(OH)2·8H2O and H2O2 by a hydrothermal synthesis method.

6. The preparation method according to claim 1, characterized in that: The weight ratio of PEG-α-CD-IA, GelMA, barium titanate nanoparticles and photoinitiator in step (2) is 1:10:5:

1.

7. The preparation method according to claim 1, characterized in that: The weight ratio of the hydrogel microspheres, pyrrole monomer and ammonium persulfate in step (3) is 10:1:

1.

8. Electromechanical coupling hydrogel microspheres prepared by the method according to any one of claims 1 to 7.

9. Use of the electromechanical coupling hydrogel microspheres according to claim 8 in preparing tissue damage repair materials.

10. The use according to claim 9, wherein the tissue damage comprises osteoarthritis.

Citation Information

Patent Citations

  • A polypyrrole nanocomposite conductive hydrogel and its preparation method

    CN109627461B

  • Application of piezoelectric hydrogel as bone glue

    CN115581813A

  • Structural protein / hyaluronic acid composite micro-nano particle, particle hydrogel material and application

    CN115521627A

Cited By

  • Hydrogel with controllable and enhanced mechanical properties as well as preparation and application of hydrogel

    CN119708545A

  • A hydrogel with controllable enhanced mechanical properties, its preparation and application

    CN119708545B